The Association Between Hospital Financial Performance and the Quality of Care - A Scoping Literature Review - Katarzyna Dubas-Jakóbczyk; Ewa Kocot; Marzena Tambor; Przemysław Szetela; Olga Kostrzewska; Richard B. Siegrist Jr; Wilm Quentin (Kerman University of Medical Sciences, 2022)
Background  Improving the quality of hospital care is an important policy objective. Hospitals operate under pressure to contain costs and might face challenges related to financial deficits. The objective of this paper was to identify and map the available evidence on the association between hospital financial performance (FP) and quality of care (Q).Methods  A scoping review was performed. Searches were conducted in 7 databases: Medline via PubMed, EMBASE, Web of Science, Scopus, EconLit, ABI/INFORM, and Business Source Complete. The search strategy combined multiple terms from 3 topics: hospital AND FP AND Q. The collected data were analysed using both quantitative and qualitative methods.Results  10 503 records were screened and 151 full text papers analysed. A total of 69 papers were included (60 empirical, 2 theoretical, 5 literature reviews, and 2 dissertations). The majority of identified studies were published within the last decade (2010-2021). Most empirical studies had been conducted in the United States (55/60), used cross-sectional approaches (32/60) and applied diverse regression models with FP measures as dependent variables, thus measuring the impact of Q on hospitals FP (34/60). The comparability of the studies' results is limited due to differences in applied methods and settings. Yet, the general overview shows that in almost half of the cases the association between hospital FP and Q was positive, while no study showed a clear negative association.Conclusion  This scoping review provides an overview of the available literature on the association between hospital FP and Q. The results highlight numerous research gaps: (1) systematic reviews and meta-analyses of existing studies with similar measures of FP and Q are unavailable, (2) further methodological/conceptual work is needed on the metrics measuring hospital FP and Q, and (3) more empirical studies should analyse the association between FP and Q in non-US healthcare settings.